If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + n + m = 2 Reorder the terms: m + n + n = 2 Combine like terms: n + n = 2n m + 2n = 2 Solving m + 2n = 2 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2n' to each side of the equation. m + 2n + -2n = 2 + -2n Combine like terms: 2n + -2n = 0 m + 0 = 2 + -2n m = 2 + -2n Simplifying m = 2 + -2n
| -3t(4t-4)+8t=3t-4 | | 7x+4=x+10 | | x=y/6(16-z) | | -27x^2+48x-5= | | 4(t-3)=2t+7 | | -2(3t-4)+3t=2t-3 | | -27x^3+48x-5= | | 10x^2+2.5x-45=0 | | 3x+11=6x-4 | | 5+6=5+x | | 6x^2-4x=-11 | | 8+y=6+2y | | -5(3t-2)+2t=4t-9 | | x^4-8x^3+98x^2-648x+1377=0 | | 36m^-4n^-6/4mn^-2p^-4 | | -x^2-100=0 | | 19=4-2m-m+7 | | (2x+4)+(3x-13)=180 | | 20a+25= | | 12-4y=2(y+9) | | 2.50x=500+0.35x | | 16a+28= | | 150x+50y=8395 | | (2a/a^2)^-2 | | 50(x+5)=a | | 200x+100y=12995 | | 3k(3k+10)=0 | | (2a/a^2)^2 | | 5x-2x=x+30 | | 3x-2=5x-19 | | 1-x=-9 | | 12a+8b= |